Ramsay Hunt Syndrome: A case report and literature review. - Oluwadaisi, Adeniyi Muyiwa; Omopariola, Olusoji A; T, Ekhosuehi A; Oyetola, Elijah O (Hasanuddin University, 2021)
BackgroundA case report of Ramsey Hunt Syndrome which is rare in dental clinic, often mis-diagnosed and not extensively documented in literature.Case presentationA case of 60-year-old woman who presented with left sided pain initially diagnosed as toothache with offending tooth extracted. However, two days after patient started having prodromal symptoms of fever, malaise followed with left facial rash, tinnitus, rash in the eternal auditory meatus, palatal and buccal painful ulcers. There was also left facial weakness, patient was treated with antiviral and steroid to good effect after 5 weeks.Conclusion:Â This case is not commonly seen in dental clinic. It highlights the possible mis-diagnosed cases of herpes zoster infection presenting as RHS. A high index of suspicion and close follow-up is essential.